Fasies Gunungapi Soputan, Daerah Kilometer Tiga Dan Sekitarnya, Kecamatan Amurang, Kabupaten Minahasa Selatan, Sulawesi Utara - Tandipajung, Jeremy; Rachmadhan, H.D. (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2024)
This research was conducted to reveal the geological characteristics and facies of volcanoes in the Kilometer Three area and its surroundings, Amurang District, South Minahasa Regency, North Sulawesi. The research area is part of Mount Soputan, one of the active volcanoes in North Sulawesi, which shows complex volcanic dynamics due to tectonic interactions between the Eurasian Plate and the Maluku Sea. Research methods include field surveys, geomorphological observations, geological mapping, petrographic analysis, and evaluation of geological structures. The results of the study identified four main geomorphological land forms, namely volcanic foothills, volcanic foothills, denunated volcanic hills, and fluvial plains. The stratigraphy in this area consists of six rock units, including alluvial units, lapili tufts, volcanic brecci, and porphyry andesite, reflecting variations in volcanic deposition and erosion processes. Analysis of geological structures reveals the presence of structures that develop due to intensive tectonic activity. Based on the distribution of volcanic materials and stratigraphic characteristics, this area is classified into the distal facies of Mount Soputan, which is characterized by the dominance of pyroclastic materials such as tuff and breccia. The geological potential of this area includes abundant stone mining resources, but it is also accompanied by geohazard risks such as landslides due to steep slope morphology and unconsolidated materials.